2020
DOI: 10.1093/qjmed/hcaa044.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum visfatin level in beta thalassemia patients

Abstract: Background Thalassemias are monogenetic hematologic disorders which are caused by faulty synthesis of one or more of the Hb chains which leads to imbalance in globin chains resulting in hemolysis and impaired erythropoiesis and chronic inflammatory condition. Visfatin is a pro-inflammatory adipocytokine which is mostly expressed in visceral adipose tissue and its testing may help in assessment of severity of the disease. Aim of the work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It also indicates the possible inflammatory role of visfatin in this condition, the possible association of this adipocytokine with endothelial and vascular dysfunction in patients with β-thalassemia, and its correlation with disease severity. 11,12 Both L-arginine and sildenafil reduced visfatin serum level after 2 months of treatment. This effect can be partly attributed to the direct anti-inflammatory effect or the ability of these drugs to prevent the progression of inflammation through vaso-modulatory mechanisms similar to that reported previously in other chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also indicates the possible inflammatory role of visfatin in this condition, the possible association of this adipocytokine with endothelial and vascular dysfunction in patients with β-thalassemia, and its correlation with disease severity. 11,12 Both L-arginine and sildenafil reduced visfatin serum level after 2 months of treatment. This effect can be partly attributed to the direct anti-inflammatory effect or the ability of these drugs to prevent the progression of inflammation through vaso-modulatory mechanisms similar to that reported previously in other chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…10 Most of these inflammatory vascular injury markers have been reported to increase in β thalassemia patients. 11,12 Therefore, inflammatory markers such as IL-1β as well as vascular endothelial markers such as serum visfatin and E-selectin levels can be useful as indicators to fully understand this mechanism and to assess the efficacy of potential therapies.…”
Section: Introductionmentioning
confidence: 99%
“…reported that sTfR levels in individuals with thalassemia were higher, but the difference was not significant [ 20 ]. Another study reported that serum ferritin levels were significantly higher in ThM but not in ThT and in the control group ( P < 0.001) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of visfatin is increased in response to infection, hypoxia, and inflammatory cytokines, and it has the potential to subsequently enhance the activation of the inflammatory cascade [ 20 , 21 ]. The current study provides evidence that individuals diagnosed with β-thalassemia major and β-thalassemia minor exhibit elevated levels of visfatin in their serum compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation